To determine whether the equation \( 3 - 5 \cdot (81\sqrt{4})^{3-4} = 3 - 6 \) is true or false, let’s simplify both sides step by step.
-
Simplify the left side \( 3 - 5 \cdot (81\sqrt{4})^{3-4} \):
- Calculate \( \sqrt{4} = 2 \), so \( 81\sqrt{4} = 81 \cdot 2 = 162 \).
- Now, evaluate the exponent: \( 3 - 4 = -1 \).
- So, we have \( (162)^{-1} = \frac{1}{162} \).
- Now plug this back into the equation: \[ 3 - 5 \cdot \frac{1}{162} = 3 - \frac{5}{162}. \]
- To combine the terms, find a common denominator: \[ 3 = \frac{486}{162} \Rightarrow 3 - \frac{5}{162} = \frac{486 - 5}{162} = \frac{481}{162}. \]
-
Simplify the right side \( 3 - 6 \):
- This is straightforward: \( 3 - 6 = -3 \).
Now we compare the left side to the right side:
- Left side: \( \frac{481}{162} \)
- Right side: \( -3 = -\frac{486}{162} \)
Since \( \frac{481}{162} \neq -\frac{486}{162} \), the left side does not equal the right side.
Therefore, we conclude that the statement is False: There is an error in calculation using the Quotient Property.
The conclusion is: False. There is an error in calculation using the Quotient Property.